Lithium cobalt oxide positive electrode material and preparation method thereof
By forming a transition metal layer vacancy in the lithium cobalt oxide material and controlling the spin state of Co3+ ions, the problems of structural phase change and irreversible oxygen loss at high voltage are solved, and the high structural stability and cycling performance of the material are improved.
Patent Information
- Application Number
- CN202311072133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-04
AI Technical Summary
The lithium cobalt oxide positive electrode undergoes structural phase change at high voltage, resulting in irreversible oxygen loss and capacity attenuation, making it difficult to maintain structural stability during the cycle.
By forming an intrinsic vacancy of the transition metal layer in lithium cobalt oxide material, and controlling the spin state of Co3+ ions from low spin to high spin, widening the spacing between the Co3d band and the O2p band, alleviating the irreversible oxygen loss phenomenon.
The structural stability and circulation performance of lithium cobalt oxide positive electrode material are significantly improved at high voltages, and the circulation life of lithium secondary batteries is extended.
Smart Images

Figure CN119560553A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of lithium secondary batteries, and in particular to a lithium cobalt oxide positive electrode material and a preparation method thereof. Background Art
[0002] At present, in order to enhance the structural stability of lithium cobalt oxide materials and improve the cycle performance of lithium secondary batteries, the industry generally performs element doping in the bulk structure of lithium cobalt oxide, utilizes bulk element doping to stabilize the material structure, and improves the reversibility of the material structure during the cycle; or coats the surface of lithium cobalt oxide, and the coated material is an electronic conductor, an ion conductor, an electronic and ion conductor, or an insulator (oxide / fluoride, etc.).
[0003] However, under high voltage, the lithium cobalt oxide positive electrode not only undergoes a structural phase transition of O3→M→H1-3→O1 (O3 phase indicates that the original structure of lithium cobalt oxide is a hexagonal system, M indicates a monoclinic system, H1-3 indicates a mixed structure of O1 and O3 phases, and O1 phase is a phase formed by the collapse of the lithium cobalt oxide structure), but also undergoes a sharp collapse of the lattice. 4+ The 3d orbital of the lattice O 2- The 2p orbital overlap is large, resulting in irreversible oxygen loss at high voltage, further exacerbating the structural deterioration and capacity decay of lithium cobalt oxide during the cycle. In current lithium-ion batteries, the lithium cobalt oxide positive electrode will not only produce a large volume change during the transition from hexagonal to monoclinic during charging, but the structural phase change is also irreversible, which will cause material structure damage and battery capacity decay. When the lithium cobalt oxide positive electrode further increases the charging voltage, due to the large overlap between the Co 3d energy band and the O 2p energy band, the Fermi level (Fm) in the delithiation state is located on the O 2p energy band, resulting in lattice oxygen oxidation, material oxygen release, and further collapse of the lithium cobalt oxide structure. Therefore, in order to improve the high-voltage cycle performance of lithium secondary batteries, it is necessary to provide a lithium cobalt oxide positive electrode material with high structural stability at high voltage. Summary of the invention
[0004] In view of this, the present invention provides a lithium cobalt oxide positive electrode material, which contains transition metal layer vacancies and has high spin Co 3+ The lithium cobalt oxide positive electrode material can have good structural stability at high voltage and can effectively improve the cycle performance of lithium secondary batteries.
[0005] The first aspect of the present application provides a lithium cobalt oxide positive electrode material, wherein the chemical formula of the lithium cobalt oxide positive electrode material is Li 1+x Co a M b Vac cO2, where M represents a metal element, Vac represents a transition metal layer vacancy, 0 ≤ x < 0.37, a + b + c + x = 1, 0.75 < a < 1, 0 < c < 0.14; the lithium cobaltate cathode material has Co with a high-spin state 3+ .
[0006] The lithium cobaltate cathode material provided by the embodiment of the present application forms an intrinsic vacancy in the transition metal layer in the lithium cobaltate material, and simultaneously regulates at least part of the Co 3+ The spin state of ions changes from low spin to high spin, broadening the energy band gap between the Co 3d energy band and the O2p energy band, thereby effectively alleviating the irreversible oxygen loss phenomenon of the material in the high delithiated state, maintaining the structural stability of the lithium cobaltate cathode material during cycling, and improving the cycling performance of the lithium cobaltate cathode material at high voltages. Using this lithium cobaltate cathode material in a lithium-ion battery can obtain a battery with both high working voltage, high capacity, and long cycle life.
[0007] Among them, the effective magnetic moment of low-spin Co 3+ is 0, and the effective magnetic moment of high-spin Co 3+ is 4.9 μ B ; the formula for calculating the effective magnetic moment is g L is the Lande factor, J is the total angular momentum, μ B is the Bohr magneton, the number of valence electron d orbital electrons of Co 3+ is 6, and the number of unpaired electrons in the high-spin state of Co 3+ is 4, and the number of unpaired electrons in the low-spin state is 0.
[0008] In the embodiment of the present application, among all Co 3+ in the lithium cobaltate cathode material, the proportion of high-spin Co 3+ is greater than 50%. High-spin Co 3+ ions can broaden the energy band gap between the Co 3d energy band and the O 2p energy band, effectively alleviating the irreversible oxygen loss phenomenon of the material in the high delithiated state, and improving the structural stability of the lithium cobaltate cathode material during cycling. In the present application, the proportion of high-spin Co 3+ in the material is controlled to be greater than 50%, which can better improve the structural stability of the lithium cobaltate cathode material during cycling.
[0009] In the present application, the magnetic susceptibility of the lithium cobaltate cathode material is measured using a vibrating sample magnetometer (VSM) in a Physical Property Measurement System (PPMS), and the Co in the lithium cobaltate cathode material can be obtained by solving through the Curie-Weiss formula3+ The ratio of high and low spin.
[0010] In the embodiment of the present application, the lithium cobalt oxide positive electrode material Co 3+ The average effective magnetic moment is greater than 3.465. In the lithium cobalt oxide positive electrode material of the present application, some Co 3+ In the low spin state, some Co 3+ is a high spin state, considering all Co 3+ , its average effective magnetic moment is greater than 3.465. 3+ The average effective magnetic moment μ=(x*0*0+(1-x)*4.9*4.9) 1 / 2 , where x represents the low-spin Co content, 0 is the low-spin Co effective magnetic moment, and 4.9 is the high-spin Co effective magnetic moment. When high and low spins each account for half, x = 0.5.
[0011] In the embodiment of the present application, M represents one or more elements selected from Fe, V, Mo, Ti, Ce, Ni, Zr, Nb, Ge, Si, Ru, Ir, and Sn. The incorporation of the above metal or semi-metal elements, wherein the variable valence element can increase the charge compensation element in the lithium cobalt oxide material, and the inert element can improve the structural stability of the lithium cobalt oxide. The element Fe can exist in the form of Fe 2+ , Fe 3+ ; The element V can exist in the form of V 2+ 、V 3+ 、V 4+ 、V 5+ ; The element Mo can exist in the form of Mo 4+ 、Mo 5+ 、Mo 6+ ; The element Ti can exist in the form of Ti 4+ ; The element Ce can exist in the form of Ce 4+ ; The element Ni can exist in the form of Ni 3+ ; The element Zr may be Zr 4+ ; The element Nb can exist in the form of Nb 3+ , Nb 4+ , Nb 5+ ; The element Ge can exist in the form of Ge 4+ ; The element Si can be Si 4+ ; The element Ru can exist in the form of Ru 4+ 、Ru 5+ ; The element Ir may be Ir 4+ , Ir 5+ ; The element Sn can exist in the form of Sn 2+ Sn 4+ .
[0012] In the embodiment of the present application, M represents Al, Ti and Mg. When M includes Al, Ti and Mg at the same time, it is beneficial to improve the cycle performance of the lithium cobalt oxide positive electrode material.
[0013] In the embodiment of the present application, the lithium cobalt oxide positive electrode material has a layered structure. The stable layered structure of the lithium cobalt oxide positive electrode material is conducive to the rapid insertion and extraction of lithium ions, and is also conducive to obtaining a higher compaction density, cycle performance, operating voltage and theoretical capacity.
[0014] Among them Li + Layer and Co 3+ The layers are arranged alternately in an orderly manner in the cubic meter of O 2- In the octahedral position formed, LiO6 and CoO6 octahedrons share edges and stack with each other. They share edges up and down, and three layers of CoO2 structure are needed to form a unit cell. + and Co 3+ There are large differences in charge and ion size, and the interaction between Co and O is stronger to form a stable layered structure.
[0015] In the embodiment of the present application, the particle size D50 of the lithium cobalt oxide positive electrode material is 14 μm-18 μm. The lithium cobalt oxide positive electrode material has a larger particle size, which is conducive to obtaining a higher compaction density. When manufacturing a battery cell, the energy density of the battery cell that can be designed is also higher, and it is conducive to obtaining a smaller specific surface area, which alleviates the side reaction between the positive electrode material and the electrolyte at high temperature.
[0016] A second aspect of the embodiment of the present application provides a method for preparing the lithium cobalt oxide positive electrode material according to the first aspect, comprising:
[0017] The lithium salt, the cobalt oxide precursor and the M source are mixed, and then calcined at 600-1200° C. for 8-15 hours, and then cooled after calcination to obtain the lithium cobalt oxide positive electrode material.
[0018] In an embodiment of the present application, the lithium salt includes one or more of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium oxide, lithium acetate, lithium chloride and lithium oxalate; the cobalt oxide precursor includes one or more of cobalt tetroxide, cobalt hydroxide, cobalt oxide and cobalt trioxide; the M source includes one or more of carbonates, oxides, hydroxides, acetates, oxalates and nitrates containing M.
[0019] In the embodiment of the present application, the cooling rate of the cooling process is greater than or equal to 10°C / min. By controlling the cooling rate of the cooling process, rapid cooling can be achieved, and transition metal layer vacancies can be obtained in the lithium cobalt oxide positive electrode material, so that at least part of the Co 3+ The spin state of the ion changes from low spin to high spin.
[0020] In the embodiment of the present application, the cooling operation includes liquid quenching. Liquid quenching can achieve rapid cooling, which is conducive to obtaining transition metal layer vacancies in the lithium cobalt oxide positive electrode material and obtaining high-spin Co 3+ Ions. The quenching liquid used in liquid quenching can be liquid nitrogen, liquid helium, ice water mixture, etc.
[0021] A third aspect of the embodiment of the present application provides a method for preparing the lithium cobalt oxide positive electrode material according to the first aspect, comprising:
[0022] The sodium salt, the cobalt oxide precursor and the M source are mixed, and then calcined at 600-1200° C. for 8-15 hours, and then cooled after calcination to obtain a sodium cobaltate compound;
[0023] The sodium cobaltate compound is mixed with a low melting point lithium salt or a lithium salt mixture, and then melted at 280-550° C. for 2-8 hours to obtain the lithium cobaltate positive electrode material; the melting point of the low melting point lithium salt or the lithium salt mixture is lower than 300° C.
[0024] In an embodiment of the present application, the sodium salt includes one or more of sodium hydroxide, sodium hydroxide hydrate, sodium carbonate, sodium nitrate, sodium oxide, sodium acetate, sodium acetate hydrate, sodium chloride and sodium oxalate; the cobalt oxide precursor includes one or more of cobalt tetroxide, cobalt hydroxide, cobalt oxide and cobalt trioxide; the M source includes one or more of carbonates, oxides, hydroxides, acetates, oxalates and nitrates containing M.
[0025] In the embodiment of the present application, the cooling rate of the cooling process is greater than or equal to 10°C / min. By controlling the cooling rate of the cooling process to achieve rapid cooling, transition metal layer vacancies can be obtained in the material, so that more Co 3+ The spin state of the ion changes from low spin to high spin.
[0026] In the embodiment of the present application, the cooling operation includes liquid quenching. Liquid quenching can achieve rapid cooling, which is conducive to obtaining transition metal layer vacancies in the lithium cobalt oxide positive electrode material and obtaining high-spin Co 3+ Ions. The quenching liquid used in liquid quenching can be liquid nitrogen, liquid helium, ice water mixture, etc.
[0027] The method for preparing the lithium cobalt oxide positive electrode material provided in the embodiment of the present application has a simple process and is easy to realize large-scale production.
[0028] The fourth aspect of the embodiment of the present application provides a positive electrode sheet, the positive electrode sheet comprising a current collector and a positive electrode active layer located on the current collector, the positive electrode active layer comprising the lithium cobalt oxide positive electrode material described in the first aspect. The positive electrode sheet can effectively improve the cycle stability by using the lithium cobalt oxide positive electrode material of the embodiment of the present application.
[0029] The fifth aspect of the embodiment of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet includes the positive electrode sheet described in the fourth aspect. The secondary battery of the embodiment of the present application is a lithium-ion secondary battery, and by adopting the positive electrode sheet of the fourth aspect of the embodiment of the present application, the cycle stability of the secondary battery is significantly improved, especially the cycle stability under high voltage (above 4.2V).
[0030] The embodiment of the present application further provides an electronic device, the electronic device comprising the secondary battery described in the fifth aspect. By adopting the secondary battery with good cycle stability of the embodiment of the present application, the market competitiveness of the electronic device can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The crystal structure diagram of conventional lithium cobalt oxide without transition metal layer vacancies;
[0032] Figure 2 A crystal structure diagram of a lithium cobalt oxide positive electrode material having transition metal layer vacancies according to an embodiment of the present application;
[0033] Figure 3 A schematic diagram of the structure of the positive electrode sheet 100 provided in an embodiment of the present application;
[0034] Figure 4 A schematic diagram of the structure of a secondary battery 200 provided in an embodiment of the present application;
[0035] Figure 5 A schematic diagram of the structure of an electronic device 300 provided in an embodiment of the present application;
[0036] Figure 6 This is a cross-sectional morphology image of a fresh (i.e., unused) positive electrode sheet prepared in Example 1 of the present application;
[0037] Figure 7 This is a cross-sectional morphology image of the positive electrode sheet prepared in Example 1 of the present application after 50 cycles at 25°C. DETAILED DESCRIPTION
[0038] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.
[0039] To improve the structural stability of lithium cobaltate materials and the cycling performance of lithium secondary batteries, the industry generally conducts element doping in the bulk structure of lithium cobaltate to stabilize the material structure using bulk element doping and improve the reversibility of the material structure during cycling; or coats the surface of lithium cobaltate with materials that are electronic conductors, ionic conductors, electronic and ionic conductors, or insulators (oxides / fluorides, etc.). However, the above methods still cannot effectively avoid the problems of the structural phase transition of O3→M→H1-3→O1 occurring in the lithium cobaltate cathode at high voltages (above 4.2V), the sharp collapse of the crystal lattice, and the irreversible oxygen loss phenomenon occurring at high voltages due to the large overlap between the 3d orbit of Co 4+ and the 2p orbit of lattice O 2- , which further exacerbates the structural deterioration and capacity decay of lithium cobaltate during cycling. Therefore, the embodiments of this application provide a lithium cobaltate cathode material that contains transition metal layer vacancies and has high-spin Co 3+ . This lithium cobaltate cathode material can have good structural stability at high voltages and can effectively improve the cycling performance of lithium secondary batteries.
[0040] The embodiments of this application provide a lithium cobaltate cathode material, and the chemical formula of this lithium cobaltate cathode material is Li 1+ x Co a M b Vac c O2, where M represents a metal or semi-metal element, Vac represents a transition metal layer vacancy, 0≤x<0.37, a + b + c + x = 1, 0.75 < a < 1, 0 < c < 0.14; this lithium cobaltate cathode material has Co 3+ ions with a high-spin state, and the effective magnetic moment of the high-spin Co 3+ ions is 4.9μ B .
[0041] The lithium cobaltate cathode material provided by the embodiments of this application forms intrinsic vacancies in the transition metal layer of the lithium cobaltate material, and at the same time regulates the spin state of at least part of the Co 3+ ions from low spin to high spin, broadening the spacing between the Co 3d energy band and the O2p energy band. Thus, it can effectively alleviate the irreversible oxygen loss phenomenon in the material under the high delithiated state, maintain the stability of the structure of the lithium cobaltate cathode material during cycling, and improve the cycling performance of the lithium cobaltate cathode material at high voltages. Using this lithium cobaltate cathode material in a lithium-ion battery can obtain a battery with both high working voltage, high capacity, and long cycle life.
[0042] Among them, the effective magnetic moment of low-spin Co 3+ ions is 0, and the effective magnetic moment of high-spin Co 3+ ions is 4.9μB ; The formula for calculating the effective magnetic moment is: g L is the Lande factor, J is the total angular momentum, μ B is the Bohr magneton, Co 3+ The number of valence electron d orbitals of the ion is 6, Co 3+ The number of unpaired electrons in the high spin state of the ion is 4, Co 3+ The number of unpaired electrons in the low-spin state of an ion is 0.
[0043] In the embodiment of the present application, all Co in the lithium cobalt oxide positive electrode material 3+ Medium and high spin Co 3+ The number of high-spin Co 3+ Ions can widen the distance between the Co 3d energy band and the O 2p energy band, effectively alleviate the irreversible oxygen loss phenomenon of the material under high lithium removal state, and improve the structural stability of the lithium cobalt oxide positive electrode material during the cycle process. 3+ The proportion of Co2O3 is controlled to be greater than 50%, which can better improve the structural stability of the lithium cobalt oxide positive electrode material during the cycle. 3+ The higher the proportion of, the more conducive to the improvement of material performance. In some embodiments of the present application, all Co in the cobalt oxide lithium positive electrode material 3+ Medium and high spin Co 3+ The proportion of all Co in the cobalt oxide positive electrode material is greater than or equal to 55%. 3+ Medium and high spin Co 3+ The proportion of all Co in the lithium cobalt oxide positive electrode material is greater than or equal to 60%. 3+ Medium and high spin Co 3+ The proportions were 51%, 53%, 55%, 60%, 65%, 67%, 68% and 70%.
[0044] It should be noted that the present application is for high spin Co in lithium cobalt oxide positive electrode materials 3+ The limitation applies to positive electrode materials at various stages, such as lithium cobalt oxide positive electrode materials before battery assembly, lithium cobalt oxide positive electrode materials in fresh batteries, and lithium cobalt oxide positive electrode materials in batteries after multiple charge and discharge cycles.
[0045] In the present application, the relationship between the magnetic susceptibility and temperature of the lithium cobalt oxide positive electrode material can be tested by a vibrating sample magnetometer (VSM) in a comprehensive physical property measurement system (PPMS), and the Curie-Weiss formula is used: χ = C / (TT C ), (where C is a constant, Tc is the Curie temperature, and T represents the temperature at which the material changes from ferromagnetism to paramagnetism), the constant C value and the Curie temperature Tc are obtained by fitting the high temperature section of the test curve, where (where N is Avogadro's constant, k B is the Boltzmann constant), according to the effective magnetic moment calculation formula: Substitute this into the effective magnetic moment of the material being measured:
[0046] according to (where x represents high spin Co 3+ The content of ions, y represents low spin Co 3+ Ion content, Represents high spin Co 3+ The effective magnetic moment of the ion, Represents low spin Co 3+ The effective magnetic moment of the ion) can be solved to obtain the Co in the lithium cobalt oxide positive electrode material 3+ The ratio of high and low spin.
[0047] In the embodiment of the present application, Co in the lithium cobalt oxide positive electrode material 3+ The average effective magnetic moment is greater than 3.465. In the lithium cobalt oxide positive electrode material of the present application, some Co 3+ In the low spin state, some Co 3+ is a high spin state, considering all Co 3+ , its average effective magnetic moment is greater than 3.465. 3+ The average effective magnetic moment μ=(x*0*0+(1-x)*4.9*4.9) 1 / 2 , where x represents the low-spin Co content, 0 is the low-spin Co effective magnetic moment, and 4.9 is the high-spin Co effective magnetic moment. When high and low spins each account for half, x = 0.5.
[0048] The chemical formula of the lithium cobalt oxide positive electrode material in this application is Li 1+x Co a M b Vac cO2, where M represents a metal or semi-metal element, Vac represents a transition metal layer vacancy, 0 ≤ x < 0.37, a + b + c + x = 1, 0.75 < a < 1, 0 < c < 0.14. a, b, c, and 1 + x represent the atomic percentages of the elements.
[0049] In some embodiments of the present application, M represents one or more metal or semi-metal elements selected from Fe, V, Mo, Ti, Ce, Ni, Zr, Nb, Ge, Si, Ru, Ir, and Sn. The incorporation of the above metal or semi-metal elements, among which variable valence elements can increase the charge compensation elements in the lithium cobaltate material, and inert elements can improve the structural stability of the lithium cobaltate. The form of existence of element Fe can be Fe 2+ 、Fe 3+ ; the form of existence of element V can be V 2+ 、V 3+ 、V 4+ 、V 5+ ; the form of existence of element Mo can be Mo 4+ 、Mo 5 + 、Mo 6+ ; the form of existence of element Ti can be Ti 4+ ; the form of existence of element Ce can be Ce 4+ ; the form of existence of element Ni can be Ni 3+ ; element Zr can be Zr 4+ ; the form of existence of element Nb can be Nb 3+ 、Nb 4+ 、Nb 5+ ; the form of existence of element Ge can be Ge 4+ ; element Si can be Si 4+ ; the form of existence of element Ru can be Ru 4+ 、Ru 5+ ; element Ir can be Ir 4+ 、Ir 5 + ; the form of existence of element Sn can be Sn 2+ 、Sn 4+ 。
[0050] In some embodiments of the present application, M represents Al, Ti, and Mg. When M includes Al, Ti, and Mg simultaneously, it is beneficial to improve the cycling performance of the lithium cobaltate cathode material.
[0051] In the embodiments of the present application, the lithium cobaltate cathode material has a layered structure. The stable layered structure of the lithium cobaltate cathode material is beneficial to the rapid insertion and extraction of lithium ions, and is also beneficial to obtaining a higher tap density, cycling performance, working voltage, and theoretical capacity.
[0052] See Figure 1 and Figure 2 , Figure 1 which is the crystal structure diagram of conventional lithium cobaltate without transition metal layer vacancies, Figure 2 and Figure 1 is the crystal structure diagram of the lithium cobaltate cathode material with transition metal layer vacancies according to the embodiments of the present application. From Figure 2 and + it can be seen that the Li 3+ layers and the Co 2- layers are alternately arranged orderly in the octahedral positions formed by the cubic close-packed O + layers. The LiO6 and CoO6 octahedrons are stacked sharing edges with each other. There are significant differences in the charge and ionic size between Li 3+ and Co Figure 1 and Figure 2 it can be seen that in the lithium cobaltate cathode material implemented in the present application, there are transition metal layer vacancies in the Co 3+ layer, and the Co 3+ layer is the transition metal layer.
[0053] In the embodiments of the present application, Vac represents the transition metal layer vacancy, that is, in the crystal structure of the lithium cobaltate cathode material, some transition metal positions in the cobalt oxide layer are vacant and not occupied. The existence of transition metal layer vacancies in the lithium cobaltate cathode material can regulate the spin state of Co 3+ ions, broaden the energy band gap between the Co 3d energy band and the O 2p energy band, effectively alleviate the irreversible oxygen loss phenomenon of the material in the highly delithiated state, and maintain the structural stability of lithium cobaltate during the cycling process. In the embodiments of the present application, 0 < c < 0.14, and the larger the value of c, the more transition metal layer vacancies in the crystal structure of the lithium cobaltate cathode material. In some embodiments of the present application, the value of c ranges from 0.01 to 0.13. In some embodiments, the value of c ranges from 0.05 to 0.12. In some embodiments, the value of c ranges from 0.08 to 0.10.
[0054] The chemical formula of the lithium cobaltate cathode material is determined by X-ray diffraction (XRD), the stoichiometric ratio is measured by an Inductive Coupled Plasma Emission Spectrometer (ICP), the elemental chemical valence state is obtained by X-ray Photoelectron Spectroscopy (XPS) or X-ray Absorption Spectroscopy (XAS), and the number of transition metal layer vacancies can be confirmed by charge conservation.
[0055] In the embodiments of the present application, 0 ≤ x < 0.37. The larger the value of x, the higher the content of Li. The higher the Li content, the more Li can be removed from the cathode material, and the higher the specific capacity of the cathode material. However, if the Li content is too high, the residual alkali on the surface of the cathode material increases, and the amount of Li deintercalation is too high, resulting in an unstable structure of the cathode material. Considering the specific capacity and structural stability of the lithium cobalt oxide cathode material comprehensively, the content of lithium x in the embodiments of the present application is controlled below 0.37. In some embodiments of the present application, the value of x ranges from 0 to 0.37. In some embodiments, the value of x ranges from 0.05 to 0.3. In some embodiments, the value of x can be, for example, 0, 0.03, 0.05, 0.09, 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.36.
[0056] In the embodiments of the present application, 0.75 < a < 1. The larger the value of a, the higher the content of Co. The higher the Co content, the higher the electronic conductivity of the cathode material, which is beneficial to electron transport. Controlling the Co content within this range is beneficial to maintaining the electron transport ability of the cathode material while ensuring the high capacity and high structural stability of the cathode material. In some embodiments of the present application, the value of a ranges from 0.78 to 0.9. In some embodiments, the value of a can be, for example, 0.76, 0.78, 0.8, 0.85, 0.9, 0.95.
[0057] In the present application, a spherical aberration corrected transmission electron microscope (Special Aberration Corrected Transmission Electron Microscope, AC-TEM) can be used to observe the atomic structure of the lithium cobalt oxide cathode material, and vacancies in the transition metal layer in the structure can be observed. In the present application, synchrotron soft X-ray absorption spectroscopy (Synchrotron soft X-ray Absorption Spectroscopy, SXAS) can be used to test the Co 3d -L edge spectrum to qualitatively observe the presence of high-spin Co 3+ ions, and the local environment information (valence state, morphology, composition, bond length, coordination number, etc.) at the atomic scale can also be tested. The present application can also use X-ray photoelectron spectroscopy (X-ray Photoelectron Spectroscopy, XPS), inductively coupled plasma emission spectrometer (Inductive Coupled Plasma Emission Spectrometer, ICP), etc. for elemental valence state, elemental qualitative and quantitative analysis.
[0058] In the embodiments of the present application, the particle size D50 of the lithium cobalt oxide cathode material is 14 μm - 18 μm. Exemplarily, the particle size D50 of the lithium cobalt oxide cathode material is 14 μm, 15 μm, 16 μm, 17 μm, 18 μm. The lithium cobalt oxide cathode material has a relatively large particle size, which is beneficial to obtaining a higher tap density. When manufacturing a battery cell, the higher the energy density of the battery cell that can be designed, and it is also beneficial to obtaining a smaller specific surface area, alleviating the side reaction between the cathode material and the electrolyte at high temperatures.
[0059] In the embodiments of the present application, the lithium cobalt oxide cathode material is a granular material, mostly irregular large single crystal particles.
[0060] The embodiments of the present application also provide a preparation method of the above lithium cobalt oxide cathode material, including:
[0061] Mixing a lithium salt, a cobalt oxide precursor, and an M source, and then calcining at 600°C - 1200°C for 8 - 15 hours. After calcination, the temperature is lowered to obtain the lithium cobalt oxide cathode material.
[0062] In the embodiments of the present application, the lithium salt may include at least one of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium oxide, lithium acetate, lithium chloride, and lithium oxalate. The cobalt oxide precursor may include at least one of cobalt tetroxide, cobalt hydroxide, cobalt oxide, and cobalt sesquioxide. The M source may include one or more of a carbonate, an oxide, a hydroxide, an acetate, an oxalate, and a nitrate containing M.
[0063] In the embodiments of the present application, the feeding ratio of the lithium salt to the cobalt oxide precursor, the lithium-cobalt molar ratio is: 1 < Li / Co < 1.6, for example, Li / Co is 1.1, 1.2, 1.3, 1.4, 1.5. Mixing the lithium salt, the cobalt oxide precursor, and the M source can be carried out by ball milling. The rotation speed r of the ball milling can be controlled at 200 rpm < r < 800 rpm, and the ball-to-material ratio is 2 - 10:1. The ball milling can be dry milling or wet milling. For wet milling, dispersants such as methanol, ethanol, isopropanol, acetonitrile, acetone, methyl butanone, and methyl isobutyl ketone can be used. The calcination can be carried out in a muffle furnace. The calcination temperature can be, for example, 600°C, 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C. The heating rate during the calcination process can be greater than 5°C / min and less than or equal to 10°C / min. For example, the heating rate during the calcination process can be 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The calcination time can be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours.
[0064] In the embodiment of the present application, the cooling rate of the cooling is greater than or equal to 10°C / min. In some embodiments of the present application, the cooling rate of the cooling can be 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min. By controlling the cooling rate of the cooling process, rapid cooling can be achieved, and transition metal layer vacancies can be obtained in the lithium cobalt oxide positive electrode material, so that at least part of the Co 3+ The spin state of the ion changes from low spin to high spin.
[0065] In the embodiment of the present application, the cooling operation includes liquid quenching. Liquid quenching can achieve rapid cooling, which is conducive to obtaining transition metal layer vacancies in the lithium cobalt oxide positive electrode material and obtaining high-spin Co 3+ Ions. The quenching liquid used in liquid quenching can be liquid nitrogen, liquid helium, ice water mixture, etc.
[0066] The present application also provides another method for preparing the above-mentioned lithium cobalt oxide positive electrode material, comprising:
[0067] Step 101, mixing the sodium salt, the cobalt oxide precursor and the M source, calcining at 600-1200° C. for 8-15 hours, and cooling after calcination to obtain a sodium cobaltate compound;
[0068] Step 102, mixing the sodium cobaltate compound with a low melting point lithium salt or a lithium salt mixture, and then melting them together at 280-550°C for 2-8 hours to obtain the lithium cobaltate positive electrode material; the melting point of the low melting point lithium salt or the lithium salt mixture is lower than 300°C.
[0069] In the embodiment of the present application, the sodium salt may be one or more of sodium hydroxide, sodium hydroxide hydrate, sodium carbonate, sodium nitrate, sodium oxide, sodium acetate, sodium acetate hydrate, sodium chloride, and sodium oxalate. The cobalt oxide precursor may be one or more of cobalt tetraoxide, cobalt hydroxide, cobalt oxide, and cobalt trioxide. The M source may be one or more of carbonates, oxides, hydroxides, acetates, oxalates, and nitrates containing M.
[0070] In the embodiments of the present application, the feeding ratio of sodium salt to cobalt oxide precursor, i.e., the molar ratio of sodium to cobalt, is: 1 < Na / Co < 1.6. For example, Na / Co can be 1.1, 1.2, 1.3, 1.4, 1.5. The mixing of sodium salt, cobalt oxide precursor and M source can be carried out by ball milling. The rotation speed r of the ball milling can be controlled within 200 rpm < r < 800 rpm, and the ball-to-material ratio is 2 - 10:1. The ball milling can be dry milling or wet milling. For wet milling, dispersants such as methanol, ethanol, isopropanol, acetonitrile, acetone, methyl butanone, methyl isobutyl ketone, etc. can be used. The calcination can be carried out in a muffle furnace. The calcination temperature can be, for example, 600 °C, 700 °C, 800 °C, 850 °C, 900 °C, 950 °C, 1000 °C, 1050 °C, 1100 °C, 1150 °C, 1200 °C. The heating rate during the calcination process can be greater than 5 °C / min and less than or equal to 10 °C / min. For example, the heating rate during the calcination process can be 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, 10 °C / min. The calcination time can be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours.
[0071] In the embodiments of the present application, the cooling rate during cooling is greater than or equal to 10 °C / min. In some embodiments of the present application, the cooling rate during cooling can be 10 °C / min, 15 °C / min, 20 °C / min, 25 °C / min, 30 °C / min, 35 °C / min, 40 °C / min. By controlling the cooling rate during the cooling process, rapid cooling can be achieved, and transition metal layer vacancies can be obtained in the material, enabling at least part of the Co 3+ ions to change from low spin to high spin.
[0072] In the embodiments of the present application, the cooling operation includes liquid quenching. Liquid quenching can achieve rapid cooling, which is beneficial to obtaining transition metal layer vacancies in the lithium cobalt oxide cathode material and obtaining high-spin Co 3+ ions. The quenching liquid used for liquid quenching can be liquid nitrogen, liquid helium, ice-water mixture, etc.
[0073] In an embodiment of the present application, when a sodium cobaltate compound is mixed with a low melting point lithium salt or a low melting point lithium salt mixture, the mass ratio of the sodium cobaltate compound to the low melting point lithium salt or the low melting point lithium salt mixture may be 4-11.3:1. In some embodiments, the mass ratio of the sodium cobaltate compound to the low melting point lithium salt or the low melting point lithium salt mixture may be 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 10.5:1, 11:1, 11.3:1. The low melting point lithium salt mixture may be, for example, a mixture of lithium nitrate and lithium chloride. The eutectic may be carried out in a muffle furnace. During the low temperature eutectic process, the sodium cobaltate compound and the low melting point lithium salt undergo Li / Na ion exchange to convert the sodium cobaltate compound into a lithium cobaltate compound. After the low temperature eutectic is completed, the reaction product is washed, centrifuged and dried to obtain a lithium cobaltate positive electrode material with transition metal layer vacancies. Wherein, the centrifugal speed can be 3000rpm / min-7000rpm / min, for example, it can be 3000rpm / min, 4000rpm / min, 5000rpm / min, 6000rpm / min, 7000rpm / min. The drying temperature can be 80-120°C, and the drying time can be 5-12h. In some embodiments, the drying temperature can be 80°C, 90°C, 100°C, 110°C, 120°C. The drying time can be 5h, 7h, 8h, 10h, 12h.
[0074] The method for preparing the lithium cobalt oxide positive electrode material provided in the embodiment of the present application has a simple process and is easy to realize large-scale production.
[0075] See also Figure 3 The embodiment of the present application further provides a positive electrode sheet 100, which includes a current collector 101 and a positive electrode active layer 102 located on the current collector 101, and the positive electrode active layer 102 includes the lithium cobalt oxide positive electrode material 10 described above in the embodiment of the present application.
[0076] In the embodiment of the present application, the current collector 101 may be aluminum foil or the like. The positive electrode active layer 102 may be made of only the above-mentioned lithium cobalt oxide positive electrode material provided in the embodiment of the present application as an active material, or may be made of the above-mentioned lithium cobalt oxide positive electrode material provided in the embodiment of the present application in combination with other positive electrode active materials as an active material. Among them, other positive electrode active materials may be commercial cobalt lithium oxide, lithium nickel oxide, lithium manganese oxide, lithium vanadium oxide, lithium iron oxide, polyanion positive electrode material, manganese nickel cobalt composite oxide, and some other ternary positive electrode materials. The positive electrode active layer 102 also includes a binder and a conductive agent.
[0077] See also Figure 4The embodiment of the present application also provides a secondary battery 200, including a positive electrode sheet 100, a negative electrode sheet 202, and a separator 203 and an electrolyte 204 located between the positive electrode sheet 100 and the negative electrode sheet 202. The secondary battery 200 of the present application is a lithium-ion secondary battery, which mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charging and discharging process, Li + The Li2O3 is inserted and deintercalated back and forth between the two electrodes. Specifically, during charging, Li + It is deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; during discharge, Li + Deintercalation from the negative electrode and intercalation into the positive electrode through the electrolyte. The secondary battery of the embodiment of the present application adopts the lithium cobalt oxide positive electrode material provided in the embodiment of the present application as the active material to prepare the positive electrode sheet. The lithium cobalt oxide positive electrode material contains transition metal layer vacancies and has high spin Co in the structure. 3+ The lithium cobalt oxide positive electrode material can maintain good structural stability during the charge and discharge cycle of repeated insertion and extraction of lithium ions, so the secondary battery can have good cycle stability performance at high voltage.
[0078] In the embodiment of the present application, the membrane 203 can be a polymer membrane such as a single-layer PP (polypropylene) film, a single-layer PE (polyethylene) film, a double-layer PP / PE, a double-layer PP / PP and a triple-layer PP / PE / PP, or a non-woven fabric, etc.
[0079] In the embodiment of the present application, the electrolyte 204 includes an organic solvent and an electrolyte lithium salt, and some additives may be added as needed. The organic solvent may be a carbonate organic solvent, such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), etc. The electrolyte lithium salt may be, for example, lithium hexafluorophosphate.
[0080] See also Figure 5 The embodiment of the present application further provides an electronic device 300, which includes a housing 301 and a secondary battery 200 contained in the housing 301, and the secondary battery 200 can supply power to the power module of the electronic device 300. Specifically, the electronic device 300 can be various consumer electronic products, including but not limited to mobile phones, tablet computers, laptop computers, wearable devices (such as glasses, bracelets, watches, etc.).
[0081] The embodiments of the present application are further described below with reference to a plurality of embodiments.
[0082] Example 1
[0083] Lithium cobalt oxide cathode material Li 1.02 Co 0.90 Al 0.03 Vac0.05 Preparation of O2:
[0084] (1) According to the stoichiometric ratio, 1.31 g LiOH, 3.878 g Co3O4 and 0.082 g Al2O3 were mixed evenly, using a planetary ball mill with a ball-to-material ratio of 5:1, ethanol as a dispersant, a ball milling speed of 400 rpm / min, a ball milling time of 5 h, 3 min rotation and 2 min rest, to obtain a mixed precursor material;
[0085] (2) Using a tablet press, the precursor material mixed in step (1) is pressed into small discs, and the discs are placed in a muffle furnace for sintering at a sintering temperature of 1000° C., a sintering time of 12 h, and a heating rate of 10° C. / min; after sintering, the sample is quickly cooled by quenching with liquid nitrogen to obtain a lithium cobalt oxide positive electrode material Li 1.02 Co 0.90 Al 0.03 Vac 0.05 O2. After testing, the lithium cobalt oxide positive electrode material Li 1.02 Co 0.90 Al 0.03 Vac 0.05 High-spin Co in O2 3+ The proportion is 60%.
[0086] Preparation of lithium secondary batteries:
[0087] The lithium cobalt oxide positive electrode material Li prepared in Example 1 1.02 Co 0.90 Al 0.03 Vac 0.05 O2, conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 92:3:5 to obtain a slurry, the slurry is coated on the surface of an aluminum foil, and after drying, it is cut into small discs of Φ12 mm to obtain a positive electrode sheet;
[0088] A metal lithium sheet (Φ14 mm), a separator (Φ16 mm), the above-mentioned positive electrode sheet and an electrolyte (120 uL) were assembled into a R2023 button cell and placed on a Xinwei tester to test the electrochemical performance.
[0089] The electrochemical performance test conditions are:
[0090] (1) Temperature: 25°C, test system: 1 st OCV 0.2C CCCV 4.65V 0.025C, 0.2C DC 3V; 2 nd -51 th 0.5C CCCV 4.65V 0.025C,0.5C DC 3V;
[0091] (2) Temperature: 45°C, test system: 1 stOCV 0.2C CCCV 4.6V 0.025C, 0.2C DC 3V; 2 nd -51 th 0.5C CCCV 4.6V 0.025C,0.5C DC 3V.
[0092] Example 2
[0093] Lithium cobalt oxide cathode material Li 1.05 Co 0.87 Al 0.05 Vac 0.03 Preparation of O2:
[0094] (1) According to the stoichiometric ratio, 3.377 g Li2CO3, 6.078 g Co3O4 and 0.222 g Al2O3 were mixed evenly, and a planetary ball mill was used with a ball-to-material ratio of 7:1, a ball milling speed of 500 rpm, a ball milling time of 6 h, and a rotation time of 3 min and a rest time of 2 min to obtain a mixed precursor material;
[0095] (2) Using a tablet press, the mixed precursor material of (1) is pressed into small discs, and the discs are placed in a muffle furnace for sintering at a sintering temperature of 1100°C, a sintering time of 12 h, and a heating rate of 10°C / min; after sintering, the sample is quickly cooled by quenching with liquid helium to obtain a lithium cobalt oxide positive electrode material Li 1.09 Co 0.87 Al 0.1 Vac 0.03 O2.
[0096] After testing, the lithium cobalt oxide positive electrode material Li 1.05 Co 0.87 Al 0.05 Vac 0.03 High-spin Co in O2 3+ The proportion is 53%.
[0097] Preparation of lithium secondary batteries:
[0098] The lithium cobalt oxide positive electrode material Li prepared in Example 2 1.05 Co 0.87 Al 0.05 Vac 0.03 O2 is used as the positive electrode active material to prepare a lithium secondary battery in the same manner as in Example 1.
[0099] Example 3
[0100] Lithium cobalt oxide cathode material Li 1.04 Co 0.88 Al 0.01 Ti 0.01 Vac 0.06 Preparation of O2:
[0101] (1) According to the stoichiometric ratio, 4.222 g Li2CO3, 7.686 g Co3O4, 0.055 g Al2O3 and 0.087 g TiO2 were mixed evenly, and a planetary ball mill was used with a ball-to-material ratio of 6:1, a ball milling speed of 400 rpm, a ball milling time of 6 h, and a rotation time of 3 min and a rest time of 2 min to obtain a mixed precursor material;
[0102] (2) Using a tablet press, the mixed precursor material of (1) is pressed into small discs, and the discs are placed in a muffle furnace for sintering. The sintering temperature is 1200°C, the sintering time is 12h, and the heating rate is 10°C / min. After the sintering is completed, the temperature is cooled at a rate of 10°C / min to obtain a lithium cobalt oxide positive electrode material Li 1.05 Co 0.88 Al 0.01 Ti 0.01 Vac 0.05 O2.
[0103] After testing, the lithium cobalt oxide positive electrode material Li 1.04 Co 0.88 Al 0.01 Ti 0.01 Vac 0.06 High-spin Co in O2 3+ The proportion is 68%.
[0104] Preparation of lithium secondary batteries:
[0105] The lithium cobalt oxide positive electrode material Li prepared in Example 3 1.04 Co 0.88 Al 0.01 Ti 0.01 Vac 0.06 O2 is used as the positive electrode active material to prepare a lithium secondary battery in the same manner as in Example 1.
[0106] Example 4
[0107] Lithium cobalt oxide positive electrode material LiCo 0.90 Al 0.02 Ti 0.01 Mg 0.01 Vac 0.06 Preparation of O2:
[0108] (1) According to the stoichiometric ratio, 5.547 g Li2CO3, 5.423 g Co3O4, 0.077 g Al2O3, 0.03 g MgO and 0.06 g TiO2 were mixed evenly, and a planetary ball mill was used with a ball-to-material ratio of 6:1, a ball milling speed of 500 rpm, a ball milling time of 5 h, and a rotation time of 3 min and a rest time of 2 min to obtain a mixed precursor material;
[0109] (2) Using a tablet press, the mixed precursor material of (1) is pressed into small discs, and placed in a muffle furnace for sintering. The sintering temperature is 1100°C, the sintering time is 12 h, the heating rate is 10°C / min, and the temperature is rapidly cooled using a 0°C ice-water mixture to obtain a lithium cobalt oxide positive electrode material LiCo 0.90 Al 0.02 Ti 0.01 Mg 0.01 Vac 0.06 O2.
[0110] After testing, the lithium cobalt oxide positive electrode material LiCo 0.90 Al 0.02 Ti 0.01 Mg 0.01 Vac 0.06 High-spin Co in O2 3+ The proportion is 67%.
[0111] Preparation of lithium secondary batteries:
[0112] The lithium cobalt oxide positive electrode material LiCo prepared in Example 4 0.90 Al 0.02 Ti 0.01 Mg 0.01 Vac 0.06 O2 is used as the positive electrode active material to prepare a lithium secondary battery in the same manner as in Example 1.
[0113] Comparative Example 1
[0114] Preparation of LiCoO2 cathode material (preparation without vacancies and high spin Co 3+ Ionic lithium cobalt oxide positive electrode):
[0115] (1) According to the stoichiometric ratio, 3.775 g Li2CO3 and 8.201 g Co3O4 were mixed evenly, using a planetary ball mill with a ball-to-material ratio of 6:1, a ball milling speed of 400 rpm, a ball milling time of 6 h, a rotation time of 3 min and a rest time of 2 min to obtain a mixed precursor material;
[0116] (2) Using a tablet press, the mixed precursor material in (1) is pressed into small discs, which are placed in a muffle furnace for sintering at a sintering temperature of 1200°C, a sintering time of 12h, a heating rate of 5°C / min, and a cooling rate of 5°C / min to obtain lithium cobalt oxide positive electrode material LiCoO2.
[0117] After testing, the high spin Co in the lithium cobalt oxide positive electrode material LiCoO2 3+ The proportion is 0.
[0118] Preparation of lithium secondary batteries:
[0119] The lithium cobalt oxide positive electrode material LiCoO2 prepared in Comparative Example 1 is used as a positive electrode active material to prepare a lithium secondary battery in the same manner as in Example 1.
[0120] The electrochemical properties of the batteries of Examples 1 to 4 and Comparative Example 1 are listed in Table 1.
[0121] Among them, the first coulombic efficiency is an indicator for evaluating the reversibility of battery cycles. During the first cycle, due to the formation of SEI film or other side reactions on the surface of the negative electrode during the charging process, this will consume a portion of the active lithium ions, resulting in the lithium ions released from the positive electrode not being able to completely return to the positive electrode during the subsequent discharge process. Calculation method: first coulombic efficiency = (first discharge specific capacity ÷ first charge specific capacity) * 100%.
[0122] The capacity retention rate after 50 cycles refers to the battery capacity after 50 cycles (termination capacity) compared with the capacity of the battery when it was fully charged (initial capacity). The percentage value is the capacity retention rate of the battery at this moment. Calculation method: Capacity retention rate = (termination capacity ÷ initial capacity) * 100%.
[0123] Table 1 Electrochemical performance comparison
[0124]
[0125] It can be seen from the results in Table 1 that, compared with the battery of Comparative Example 1, the batteries of Examples 1 to 4 of the present application have significantly improved capacity retention rates at room temperature 25°C and high temperature 45°C. This is because the lithium cobalt oxide positive electrode material used in the battery of the present application embodiment forms intrinsic vacancies in the transition metal layer in the lithium cobalt oxide material, while regulating at least part of the Co 3+ The spin state of the ions changes from low spin to high spin, widening the distance between the Co 3d energy band and the O 2p energy band, thereby effectively alleviating the irreversible oxygen loss phenomenon of the material in the high de-lithiation state, maintaining the structural stability of the lithium cobalt oxide positive electrode material during the cycle, and improving the cycle performance of the lithium cobalt oxide positive electrode material under high voltage. Comparing Example 1 and Example 2, it can be seen that the lithium cobalt oxide positive electrode material of Example 1 has more transition metal layer vacancies and higher high spin Co 3+ The ion ratio is increased, and the high voltage cycle performance at room temperature 25°C and high temperature 45°C is improved. Comparing Example 3 with Example 4, it can be seen that M being Al, Ti and Mg can better improve the cycle performance of the lithium cobalt oxide positive electrode material.
[0126] Figure 6 This is a cross-sectional morphology image of a fresh (i.e., unused) positive electrode sheet prepared in Example 1 of the present application; Figure 7This is a cross-sectional morphology image of the positive electrode sheet prepared in Example 1 of the present application after 50 cycles at 25°C; Figure 6 and Figure 7 It can be seen that the positive electrode sheet prepared in the embodiment of the present application has little difference in morphology and structure before and after the cycle, the structure of the lithium cobalt oxide positive electrode material is stable, and there is no collapse of the lithium cobalt oxide positive electrode material.
[0127] It should be understood that the first, second and various numerical numbers involved in this document are only distinguished for the convenience of description and are not used to limit the scope of the present application.
[0128] In this application, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0129] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0130] In this application, “-” represents a range value, including the endpoint values at both ends. For example, the value of a can be 0.5-15, which means that the value of a can be between 0.5 and 15, and includes the endpoint values 0.5 and 15.
[0131] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
Claims
1. A lithium cobalt oxide positive electrode material, characterized in that: The chemical formula of the lithium cobalt oxide cathode material is Li 1+ x Co a M b Vac c O2, where M represents a metal and / or semi-metal element, Vac represents a transition metal layer vacancy, 0 ≤ x < 0.37, a + b + c + x = 1, 0.75 < a < 1, 0 < c < 0.14; the lithium cobalt oxide cathode material has Co with a high-spin spin state 3+ .
2. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The high spin Co 3+ The effective magnetic moment is 4.9μ B All Co in the lithium cobalt oxide positive electrode material 3+ Medium and high spin Co 3+ The number accounts for more than 50%.
3. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The lithium cobalt oxide positive electrode material Co 3+ The average effective magnetic moment is greater than 3.465, and the average effective magnetic moment μ=(x*0*0+(1-x)*4.9*4.9) 1 / 2 , where x represents the low-spin Co content, 0 is the low-spin Co effective magnetic moment, and 4.9 is the high-spin Co effective magnetic moment.
4. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The M represents one or more metal or semi-metal elements selected from Fe, V, Mo, Ti, Ce, Ni, Zr, Nb, Ge, Si, Ru, Ir, and Sn.
5. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The M represents Al, Ti and Mg.
6. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The lithium cobalt oxide positive electrode material has a layered structure.
7. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The particle size D50 of the lithium cobalt oxide positive electrode material is 14 μm-18 μm.
8. The method for preparing the lithium cobalt oxide positive electrode material according to any one of claims 1 to 7, characterized in that: include: The lithium salt, the cobalt oxide precursor and the M source are mixed, and then calcined at 600-1200° C. for 8-15 hours, and then cooled after calcination to obtain the lithium cobalt oxide positive electrode material.
9. The preparation method according to claim 8, characterized in that: The lithium salt includes at least one of anhydrous lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium nitrate, lithium oxide, lithium acetate, lithium chloride and lithium oxalate; the cobalt oxide precursor includes at least one of cobalt tetroxide, cobalt hydroxide, cobalt oxide and cobalt trioxide; the M source includes at least one of carbonates, oxides, hydroxides, acetates, oxalates and nitrates containing M.
10. The preparation method according to claim 8, characterized in that: The cooling rate of the cooling is greater than or equal to 10°C / min.
11. The preparation method according to claim 8, characterized in that: The temperature reduction operation includes liquid quenching.
12. The method for preparing a lithium cobalt oxide positive electrode material according to any one of claims 1 to 7, characterized in that: include: The sodium salt, the cobalt oxide precursor and the M source are mixed, and then calcined at 600-1200° C. for 8-15 hours, and then cooled after calcination to obtain a sodium cobaltate compound; The sodium cobaltate compound is mixed with a low melting point lithium salt or a lithium salt mixture, and then melted at 280-550° C. for 2-8 hours to obtain the lithium cobaltate positive electrode material; the melting point of the low melting point lithium salt or the lithium salt mixture is lower than 300° C.
13. The preparation method according to claim 12, characterized in that: The sodium salt includes at least one of sodium hydroxide, sodium hydroxide hydrate, sodium carbonate, sodium nitrate, sodium oxide, sodium acetate, sodium acetate hydrate, sodium chloride and sodium oxalate; the cobalt oxide precursor includes at least one of cobalt tetroxide, cobalt hydroxide, cobalt oxide and cobalt trioxide; the M source includes at least one of carbonate, oxide, hydroxide, acetate, oxalate and nitrate containing M.
14. The preparation method according to claim 12, characterized in that: The cooling rate of the cooling is greater than or equal to 10°C / min.
15. The preparation method according to claim 12, characterized in that: The temperature reduction operation includes liquid quenching.
16. A positive electrode sheet, characterized in that: The positive electrode sheet comprises a current collector and a positive electrode active layer located on the current collector, and the positive electrode active layer comprises the lithium cobalt oxide positive electrode material according to any one of claims 1 to 7.
17. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises the positive electrode sheet according to claim 16.
18. An electronic device, characterized in that: The electronic device comprises the secondary battery according to claim 17.